Pengelolaan Sumber Daya Manusia di Era Digital pada Usaha Mikro Kecil dan Menengah - Ridfan Rifadly Abadi; Agung Widhi Kurniawan; Muhammad Ichwan Musa; Rezky Amalia Hamka; Khaidir Syahrul (EMPOWERMENT: Journal of Community Practice, 2025)
This community service activity aims to provide an understanding of the importance of human resource management in the digital era and strategies that can be applied in Kassi Village, Rumbia District, Jeneponto Regency in facing the development of the digital economy by utilizing digital tools systems, skilled in using several digital platforms, such as: cloud-based cashier applications, social media applications, tools for data analysis, and so on. The method used in this community service is first by conducting direct observation and conducting counseling and training on how to increase the competitiveness of UMKMs through strategies building digital infrastructure, increasing digital literacy, building a digital work culture, creating a digital entrepreneurial ecosystem, and developing digital talent. The results of this activity are very useful because they can increase the insight and knowledge of UMKM actors. In addition, the support and motivation from the Head of Kassi Village made UMKM actors very enthusiastic in participating in the training.